Open appendicectomy stump: invaginate or not to invaginate? - Suvera, Mukesh S.; Kharadi, Ashish H.; Asari, Unnati S.; Damor, Panchshila B.; Shah, Mihir T.; Patel, Mansukh B. (International Journal of Research in Medical Sciences, 2017)
Acute appendicitis remains the most common abdominal surgical emergency. Appendicectomy is the standard treatment of acute appendicitis, which performed by open or laparoscopic approach. During open method, after removal of appendix, stump simple ligation or simple ligation and invagination. A prospective randomized study conducted at Smt SCL General Hospital, Smt NHL municipal Medical College, Ahmedabad between October 2009 to September 2011 to evaluate the necessity of appendicular stump invagination during appendicectomy. A total 110 patients were studied and randomized into two group, Group I stump simple ligation, transfixation and invagination and Group II stump simple ligation and transfixation only. There was no statically significant difference in the rate of postoperative complication and post operative hospital stay between the two groups. The mean operating time was significantly shorter in group without invagination. The rate of postoperative paralytic ileus was more in group I. We conclude that simple ligation of the appendicular stump during appendicectomy is safe, simple and shortens operating time.